Aztec antichrist : performing the apocalypse in early colonial Mexico - Leeming, Ben (IMS monograph, 2022)
"In Aztec Antichrist, Ben Leeming presents a transcription, translation, and study of two Nahuatl Antichrist plays that are likely the earliest surviving presentations of the Antichrist legend in the Americas, and possibly the earliest surviving play scripts in the whole of the New World in any language"--